2021
DOI: 10.3390/molecules26195973
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Sensitizes Cholangiocarcinoma Cells to Be Killed by Natural Killer-92 (NK-92) Cells

Abstract: Immunotherapy harnessing immune functions is a promising strategy for cancer treatment. Tumor sensitization is one approach to enhance tumor cell susceptibility to immune cell cytotoxicity that can be used in combination with immunotherapy to achieve therapeutic efficiency. Cordycepin, a bioactive compound that can be extracted from some Cordyceps spp. has been reported to effectively inhibit tumor growth, however, the mechanism of its tumor sensitization activity that enhances immune cell cytotoxicity is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…CD56 expressing EVs in the circulation of CCA patients were enhanced compared to HVs, and not specifically changed by SIRT. There are ongoing approaches to apply NK cell stimulating substances in the therapy of CCA [ 51 ]. However, our current data do not reflect a significant relevance of SIRT as a potential stimulating factor of those cells or their enhanced communication via EVs in CCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…CD56 expressing EVs in the circulation of CCA patients were enhanced compared to HVs, and not specifically changed by SIRT. There are ongoing approaches to apply NK cell stimulating substances in the therapy of CCA [ 51 ]. However, our current data do not reflect a significant relevance of SIRT as a potential stimulating factor of those cells or their enhanced communication via EVs in CCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this improvement of NK killing activity was found in perforin-deficient NK cells and could be inhibited by neutralizing antibodies to FasR and TRAIL-R, suggesting the NK cell-mediated cytotoxicity was promoted through TRAIL- and Fas-death receptor pathway [ 59 ]. Previous studies from our group, the increase of TRAIL-R after cordycepin treatment [ 22 ] and FasR after doxorubicin [ 21 ] associated with improvement of NK-92 cell killing activity in CCA and breast cancer, respectively, which emphasized the potential of FasR and TRAIL-R2 (DR5) modulation on NK cell killing activity. In this study, we demonstrated the effect of genistein on increasing either FasR or TRIAL-R expression in which the change of FasR expression was predominated in three cell lines over that of TRAIL-R ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 63%
“…Recently, our group reported the immunosensitization effect of cordycepin, a bioactive compound of some Cordyceps spp. [ 22 ]. At a comparable concentration to genistein, cordycepin greatly increased the TRAIL-R expression and significantly improved the NK function to kill KKU213A but not KKU055 and KKU100 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations